MiR-33b inhibits osteosarcoma cell proliferation through suppression of glycolysis by targeting Lactate Dehydrogenase A (LDHA) - Zheng, Xin-Min; Xu, Chun-Wei; Wang, Fei (Cellular and Molecular Biology, 2018)
Osteosarcoma (OS) is one of the most common types of malignant bone tumor in adolescent. MicroRNAs (miRNAs) are widely studied regulatory molecules which play important roles in tumor development, differentiation, growth, invasion, chemosensitivity and cellular metabolism. Recently, miR-33b has been reported to act as a tumor suppressor in osteosarcoma. However, the detailed mechanism of miR-33b in regulating osteosarcoma cell proliferation remains unclear. In this study, we detected miR-33b was significantly downregulated in osteosarcoma tissues compared to their matched adjacent nontumor tissues. The decreased expressions of miR-33b were also found in multiple osteosarcoma cell lines, including MG63, Saos-2, U2OS and SOSP-9607 when compared to normal osteoblast cell line hFOB. Overexpression of miR-33b suppressed U2OS cell proliferation and anaerobic glycolysis. We identified Lactate dehydrogenase-A (LDHA) as a direct target of miR-33b in osteosarcoma tumors and cells by Western blot and luciferase assay. Moreover, inhibition of LDHA significantly suppressed glycolysis and cell proliferation of osteosarcoma cells. Restoration of LDHA in miR-33b-overexpressing osteosarcoma cells reversed the suppressive effect of miR-33b on cell proliferation. In addition, we report a significantly negative correlation between LDHA mRNA and miR-33b expression in osteosarcoma tumors: miR-33b is downregulated in OS tumors with high levels of LDHA (92.9%). Meanwhile, high miR-33b expressions were found majorly in OS tumors with low LDHA mRNA levels (82.4%). This study reveals that miR-33b plays a suppressive role in the regulation of osteosarcoma cell proliferation through direct targeting LDHA. The miR-33b/glycolysis/LDHA axis may contribute to development of therapeutic anti-tumor agents for osteosarcoma.